Becoming an Intercultural Doctoral Student: Negotiating Cultural Dichotomies - Bui, Tram Anh (Journal of International Students, 2021)
International students experience both challenges and possibilities when they situate themselves in new sociocultural environments. The process of intercultural learning affects their self-formation and construction of their multiple identities. This self-reflective paper examines my experience as an international doctoral student transitioning from a Vietnamese cultural background to Canadian culture. By using concentric storying to deconstruct my journal entries, I found recurrent themes of conflicts and tensions emerging through different dialectical processes in my journey of becoming an intercultural doctoral student. My intercultural learning exposed my vulnerable self while I searched for my core values and beliefs. This journey has brought profound changes in making meaning of my adventure in transnational space. My story may shed light on the understanding of life in transition and provide direction for other international doctoral students seeking to enhance their intercultural competence in a similar educational landscape.